The ASEAN Economic Community and the European experience - Michael G. Plummer; Reid W. Click (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2006)
In November 2002, it was proposed at the Association of Southeast Asian Nations (ASEAN) Heads of Government meeting in Phnom Penh that the region should consider the possibility of creating an ASEAN Economic Community (AEC) by 2020. The name is evocative, for an Economic Community immediately brings to mind the European experience. In fact, when the Asian Pacific Economic Cooperation (APEC) was re-inventing itself, it was proposed that the words behind the organization's acronym be replaced with Asia-Pacific Economic Community. This idea was rejected explicitly for fear that it would give the impression that APEC was intending to move in the direction of the EC model, which was thought to be too controversial.
Keywords: 330